Climate-responsive vector control strategies for Aedes albopictus - Jesús Bellver-Arnau; Laura Blanco-Sierra; Santi Escartin; Simone Mariani; Frederic Bartumeus (Parasites & Vectors)
Abstract Background The rise in mosquito-borne diseases such as dengue, Zika, and chikungunya, exacerbated by the ever-expanding habitats of Aedes albopictus, poses a significant public health risk. Even marginal improvements in vector control efficacy can be crucial in mitigating these risks. Methods In this study, we employed a metapopulation model to simulate Ae. albopictus population dynamics and dispersal, optimizing the timing and spatial allocation of larvicidal treatments. Results Simulations revealed that larvicide treatments are most effective when applied preventively, early in the mosquito season, particularly under conditions of lower-than-average cumulative rainfall and, to a minor extent, colder-than-average temperatures, as these conditions limit larvae proliferation. We found that breeding site characteristics, particularly surface area and maximum water holding capacity, are critical in determining optimal treatment allocation in scarce-resource scenarios. However, a cost-effectiveness trade-off exists, as larger breeding sites offer more substantial reductions in mosquito populations but also demand higher larvicide dosages. Spatial factors such as breeding site distribution had minimal impact on treatment efficacy, possibly due to the high mobility range of adult mosquitoes compared with the size of the study area. Conclusions Our results highlight the superior efficiency of the optimized approach in comparison with routine vector control strategies, especially when resources are limited, offering a more effective use of larvicide in controlling mosquito populations. This study demonstrates that vector control strategies for Ae. albopictus can be significantly enhanced by considering climatic variables and breeding site characteristics in treatment planning. This research provides a framework for developing cost-effective and flexible mosquito control programs that can adapt to environmental conditions, potentially improving public health outcomes by reducing the transmission risk of mosquito-borne diseases. Graphical Abstract